Pengaruh Disiplin Kerja Dan Motivasi Kerja Terhadap Kinerja Karyawan PT. Tiki Jalur Nugraha Eka Kurir - Sri Haryanti Lubis; Heryenzus Heryenzus (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2020)
Human Resource Management (HRM) has an obligation to build conducive behavior for employees. In addition, HRM also has a duty to create the best performance for companies and employees. Employee performance is not only the result of work achieved by a person in carrying out the tasks assigned to him but includes the process of how the work takes place to achieve work results. Employee performance is said to be important because it can be used to find out and assess the extent to which employees can carry out tasks and jobs that have been given by the company. One of the things that affects employee performance is work discipline and work motivation. Therefore, a study was conducted on the performance of employees of PT Tiki Lintas Nugraha Eka Kurir Batam employees who were influenced by work discipline and work motivation. This study uses research designs arranged in order to produce a systematic picture of scientific information sourced from the subject or object of research. This descriptive research will focus on the systematic explanation of the facts that have been obtained during the research carried out. After the data is processed through the method of data analysis, this thesis report has shown these two variables have a significant effect on employee performance, which means that employee performance is affected by work discipline and work motivation, while the rest is influenced by other variables not examined in this study.